2022
DOI: 10.3390/jof8070693
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of CRISPR/Cas9 Genome-Editing System Based on Dual sgRNAs in Flammulina filiformis

Abstract: Flammulina filiformis, previously known as Asian Flammulina velutipes, is one of the most commercially important edible fungi, with nutritional value and medicinal properties worldwide. However, precision genome editing using CRISPR/Cas9, which is a revolutionary technology and provides a powerful tool for molecular breeding, has not been established in F. filiformis. Here, plasmids harboring expression cassettes of Basidiomycete codon-optimized Cas9 and dual sgRNAs targeting pyrG under the control of the gpd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Boontawon et al established an efficient CRISPR/Cas9-assisted genome-editing system based on plasmid harboring expression cassettes of Cas9 and different single-guide RNAs in P. ostreatus [ 30 ]. Liu et al reported a CRISPR/Cas9 genome-editing system based on a plasmid delivery strategy in F. filiformis but only two mutants were obtained in their study [ 2 ]. The transformation efficiency of the plasmid method is relatively low, and there are many false positives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Boontawon et al established an efficient CRISPR/Cas9-assisted genome-editing system based on plasmid harboring expression cassettes of Cas9 and different single-guide RNAs in P. ostreatus [ 30 ]. Liu et al reported a CRISPR/Cas9 genome-editing system based on a plasmid delivery strategy in F. filiformis but only two mutants were obtained in their study [ 2 ]. The transformation efficiency of the plasmid method is relatively low, and there are many false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the plasmid method used with F. filiformis required up to 28 d for the transformants to grow after PEG-mediated transformation [ 2 ]. However, in our RNP complex method, transformant growth occurred after only 11 d. The reason for this difference is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ge et al P.M. Wang et al) [ 1 ], also known as golden needle mushroom or winter mushroom, is one of the most produced and consumed edible mushroom species in China [ 2 , 3 ]. It is also a species of great interest in macrofungus research today [ 4 , 5 ]. With the gradual application of industrialized large-scale production of F .…”
Section: Introductionmentioning
confidence: 99%